Representative and Commissive Illocutionary Acts in Donald Trump’s Inauguration Speech - Sekar Pratiwi Putri, Putu Diah (Humanis; Vol 22 No 4 (2018), 2018)
This paper is entitled Representative and Commissive Illocutionary Acts in Donald Trump’s Inauguration Speech. The aims of this study are to find out the classification and the intended meaning of the representative and commissive illocutionary act found in the speech. The research method used in the study was qualitative analysis method. The data were collected from the Donald Trump’s inauguration speech transcript and then identified the function of the illocutionary act and explained the intended meaning. Based on the analysis, the functions of the representative illocutionary act that were found are stating, predicting. affirming, describing and denying. Meanwhile, the function types of commissive illocutionary act are assuring, promising and pledging. The intended meanings that were found in the context of situation analysis are presenting, unifying, revealing, clarifying, convincing and committing.